UPAYA PENANGANAN BERSIHAN JALAN NAPAS MELALUI MANAJEMEN JALAN NAPAS PADA PASIEN YANG MENGALAMI INFEKSI OPORTUNISTIK: LITERATUR REVIEW - Nuriya Nuriya; Agis Taufik (CV. ADIBA AISHA AMIRA, 2022)
Introduction: AIDS is a disease caused by Immunodeficiency Virus that can weaken a person's immune system and make susceptible to various diseases. TB is one of the opportunistic infections experienced by people with HIV / AIDS. Pulmonary tuberculosis oftenoccurs a buildup of secretions that cause problems with ineffectiveness of airway cleaning so this is needed treatment that can help in removing sputum. Purpose: This study aims to conducta literature review on some literature on the effective effects of coughing on patients with ineffectiveness of airway nets. Method: A systematic review was conducted with the PICO model in April 2022. Literature collection is done by browsing the PubMed database of (n:20) articles, Sciencedirect (n:3) articles, and Google Scholar (n:6) articles. So that the number of articles as many as 29 articles. However, only 5 articles that fit the author's inclusion criteria in the last 5 years, free full text, appropriate themes and original reviews. Keywords used: